The quality of the living environment versus natural factors – the case study of Olsztyn - Wasilewicz-Pszczółkowska, Monika; Szczepańska, Agnieszka (International Conference “Environmental Engineering”, 2017)
Current social requirements concerning the living environment tend to be more and more related to the natural values of the urban space. People are aware of the fact that contact with nature is extremely important for of mental and physical health. Therefore, the quality of the natural environment around the place of living influences the quality of life. The studies confirm that the presence of natural elements in the urban space may expressly affect the improvement of this quality. An example of a city with high quality of life is represented by Olsztyn, the capital of the Warmian-Masurian Province, located within the borders of the functional area of the Green Lungs of Poland, which is characterized by the particularly valuable quality of its natural environment. This is confirmed by the results of the social Diagnosis dated 2015, which put Olsztyn in 4th place among the largest Polish cities in the ranking concerning the quality of life. It is also influenced by the quality of the natural environment, which in the case of Olsztyn is manifested in a large number of green areas and standing bodies of water located within the administrative borders of the city. The aim of this paper is to compare the quality of the living environment of individual boroughs of Olsztyn conditioned by the natural elements (greenery, bodies of water, air, noise) in relation to the received public opinion polling results.